2018
DOI: 10.1186/s12913-018-3174-y
|View full text |Cite
|
Sign up to set email alerts
|

Health care provision for refugees in Germany – one-year evaluation of an outpatient clinic in an urban emergency accommodation

Abstract: BackgroundIn 2015, Germany recorded the highest rates of refugees since the early 1990s. Access to medical care is a legally regulated fundamental element of aid for refugees. In practice, there are several hurdles such as language barriers and legal regulations. In response to the massively increased need, special outpatient services for refugees were started in several German cities. In Cologne, an outpatient clinic (OPD) was established in the largest emergency accommodation centre for refugees supported by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 8 publications
3
50
0
2
Order By: Relevance
“…The highest amount of provided medical care was related to infections, which is in line with most cross-sectional observations [ 14 , 23 ]. Non-communicable diseases (ICPC-2 category ‘other diagnoses’) comprised one-fifth of provided medical care.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The highest amount of provided medical care was related to infections, which is in line with most cross-sectional observations [ 14 , 23 ]. Non-communicable diseases (ICPC-2 category ‘other diagnoses’) comprised one-fifth of provided medical care.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the applicability of our data we note that virtually all published studies on health care at refugee camps provided consultation-based data that use given diagnoses of a consultation as a proxy of disease prevalence [ 8 , 23 ]. The expenditure of time and workforce may be underestimated through such a consultation-based analysis.…”
Section: Discussionmentioning
confidence: 99%
“…An outpatient clinic at an emergency accommodation in Cologne, for example, reported a higher rate of headache, back/neck problems and abdominal pain than found in our study. 23 The difference between our study and many other studies might be explained by the fact that the consultations at our walk-in clinic were guided by the patients’ self-reported reasons for consultation and that there was no general screening for psychological disorders. Studies including general screenings reported that almost half of the recently arrived refugees in Germany screened positive for post-traumatic stress disorder, depression or somatisation.…”
Section: Discussionmentioning
confidence: 64%
“…In the operation of these concepts, studies have mostly focused on single dichotomous variables referring to the use or non-use of a single service (e.g., Correa-Velez and Ryan, 2012;Michaan et al, 2014;Choi et al, 2015). A few studies have focused on the comparison of user rates, analysing frequency rates with regard to different facilities (Kiss et al, 2013) or different services (Borgschulte et al, 2018).…”
Section: Health Service Utilizationmentioning
confidence: 99%
“…Meta‐reviews have concluded that such utilization is “limited” and “late” (Carolan, : 411), “low” (Correa‐Velez and Ryan, : 14) and “less” and “later” than user rates of host country citizens (e.g., Munro et al., : 283). Numerous case studies also point to refugees’ problematic or low utilization of health services (e.g., Asgary and Segar, ; Correa‐Velez and Ryan, ; Michaan et al., ; Choi et al., ; Langlois et al., ; Gottlieb et al., ), although a few studies argue that there is “no evidence of under‐use” (Kiss et al., : 57), that access for refugees is “relatively good” (El Arab and Sagbakken, ), and that refugees’ demands for health services are “largely met” (Borgschulte et al., : 6). The findings of both positive and negative health service utilization in host countries begs the question of how such use is conceptualized and operationalized, as well as how it is contextualized, that is, what country‐specific legislation relates to refugees and their entitlement to health services in the host country.…”
Section: Introductionmentioning
confidence: 99%